Short-Run Demand for Palestinian Labor - Angrist, Joshua D. (Journal of Labor Economics, 1996)
Palestinian residents of the West Bank and Gaza Strip who work in Israel generally earn more than Palestinians employed locally, but this wage premium is highly volatile. Beginning with the 1987 Palestinian uprising, changes in wage differentials by work location parallel Palestinian absences from work in Israel. This article interprets changing location differentials in response to exogenous shocks as movements along an Israeli demand curve for migrant workers. Estimates of a model of the West Bank and Gaza Strip labor market are used to evaluate the effect of policies governing Palestinian access to the Israeli labor market.